2011
DOI: 10.1007/s00264-011-1354-z
|View full text |Cite
|
Sign up to set email alerts
|

Arthroplasty options in femoral-neck fracture: answers from the national registries

Abstract: Our review of data from national registries supports the continued use of bipolar hemiarthroplasty in femoral-neck fracture in the elderly and identifies age, method of fixation and surgical approach as important prognostic variables in determining implant survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 15 publications
1
58
1
3
Order By: Relevance
“…Another complication was acetabular erosion, which was believed to cause pain and impaired hip function [12]. Data from national registries indicate that only 5.1 % of revisions in Australia and 4.7 % in Sweden were attributable to acetabular erosion [24]. In theory, bipolar HA reduces stress on the acetabular surface and thereby reduces acetabular erosion.…”
Section: Discussionmentioning
confidence: 99%
“…Another complication was acetabular erosion, which was believed to cause pain and impaired hip function [12]. Data from national registries indicate that only 5.1 % of revisions in Australia and 4.7 % in Sweden were attributable to acetabular erosion [24]. In theory, bipolar HA reduces stress on the acetabular surface and thereby reduces acetabular erosion.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable studies do not report on the outcome for patients who are living and those who have not undergone revision surgery [6,11,15,20]. LaBelle et al [13] reported a 10% Fig. 1 The graph shows the cumulative incidence of revision when patient death was considered as a competing risk (20-year rate = 3.5%).…”
Section: Discussionmentioning
confidence: 99%
“…The radiographic data showed that the implants continued to function well mechanically at long-term followup in the few remaining patients. Because some studies of bipolar hemiarthroplasties are registry-based, they do not include a radiographic analysis [6,12,13,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On failure of these operations, a THR is indicated but the effect of these implants on the operative procedures and long-term outcomes of a subsequent THR has been debatable and not clear. 1,2 The conversion of failed hip hemiarthroplasty to THR has been associated with high rates of intra-and postoperative complications. 3,4 However, clinical experience has defined specific recurrent patterns of failure of hip hemiarthroplasty, 5,6 but there is no classification of these failures.…”
Section: Introductionmentioning
confidence: 99%